Estrategias metodológicas para el aprendizaje del Movimiento Armónico Simple, Carrera de Pedagogía de las Ciencias Experimentales: Matemáticas y la Física. - Ocapana Moyota, Marco Antonio (2024)
The research addresses "Methodological strategies for learning Simple Harmonic Motion, Pedagogy of Experimental Sciences: Mathematics and Physics." The general objective is to propose micro-curricular planning incorporating methodological strategies to improve learning in Fifth Semester students. The methodology used is quantitative, with a non-experimental design and a descriptive-propositional level. It implies a detailed analysis of the strategies used and the creation of micro-curricular planning implemented methodological strategies that serve the learning of the MAS. The population is made up of students of the Pedagogy Career of Experimental Sciences: Mathematics and Physics; the survey carried out on students identified key strategies; in addition, the detailed integration of these strategies provides a clear guide for the development of micro planning curricular, promoting deep and meaningful understanding. The research seeks to improve the learning process of Simple Harmonic Motion through specific methodological strategies, theoretically supported and adapted to micro-curricular planning for students of Pedagogy of Experimental Sciences: Mathematics and Physics.